(untitled) (Panacea Journal of Medical Sciences, 2024)
Background: Pyoderma is an infection of skin or its appendages. Staphylococcus aureus and Streptococcus pyogenes are most common causative agents of Community acquired Pyoderma and Gram negative bacilli are encountered to lesser extent. Emergence of drug resistance has caused increased morbidity and therapeutic challenge in the management of pyoderma cases. Hence the present study is undertaken to know the bacterial profile of Community acquired pyoderma and their antibiotic susceptibility pattern in our set up using conventional techniques. Materials and Methods : Pus Samples were processed as per the standard microbiological procedures over a period of one and half year. Antibiotic susceptibility tests were performed by Kirby-Bauer disk diffusion method following CLSI guidelines. Results : out of 150 pus samples, 105 (70%) were primary pyoderma cases and 45 (30%) were secondary. Most affected age group is 0 to 10 years (25.33%) followed by 11 to 20 years (18%). S.aureus (70%) is the most commonly isolated which showed highest resistance towards Penicillin (81.91%) followed by Erythromycin, Ciprofloxacin (55.24%), Amoxicillin-Clavulanic Acid and Ofloxacin (37.14%), Cefepime (29.53%), Cotrimoxazole (26.67%). Lesser resistance was shown against Tetracycline (14.29%), Gentamycin (11%), Clindamycin (06.67%) and Chloramphenicol (02.86%). No resistance was shown against Linezolid. Rate of MRSA was 24.76%. Conclusion: Present study reveals that children are at higher risk of developing pyoderma and S. aureus is the commonest causative agent in our geographical area with considerably high prevalence of MRSA. Isolates are resistant to commonly used topical agents like erythromycin. Systematic surveillance of antimicrobial susceptibility will help in effective management of cases and emergence of drug resistance.